Investigation of microbial profile, levels of endotoxin and lipoteichoic acid in teeth with symptomatic irreversible pulpitis: a clinical study. (27th September 2020) - Arruda‐Vasconcelos, R.; Louzada, L. M.; Feres, M.; Tomson, P. L.; Cooper, P. R.; Gomes, B. P. F. A.
Abstract: Aim: To investigate the microbial profile, and levels of endotoxin (LPS) and lipoteichoic acid (LTA), in infected dentine (ID) and root canals (RC) at different phases of root canal treatment in teeth with symptomatic irreversible pulpitis. Methodology: Ten volunteers were included, and samples were collected from infected dentine (ID) and the root canal lumen (RC) using sterile excavators and paper points, respectively. RC samples were taken before (S1) and after (S2) chemo‐mechanical canal preparation (CMP), and after intracanal medication (ICM; S3). Checkerboard DNA‐DNA hybridization was used for microbial analysis. The levels of LPS and LTA were evaluated using the limulus amebocyte lysate assay and ELISA, respectively. Shapiro–Wilk's test was used to verify data normality. Friedman's test was used to evaluate statistical differences using checkerboard DNA‐DNA hybridization in the ID and RC at the different phases of the RC treatment. Post hoc Dunn's multiple comparison test was used to verify significant differences recorded at the different time‐points. The levels of LPS and LTA were analysed statistically by using repeated measures anova and Tukey's post hoc test to evaluate differences in both sites. The significance level was set at 5% ( P  < 0.05). Results: A total of 40 DNA probes were used for microbial investigation of ID and RC samples using checkerboard DNA‐DNA hybridization. The levels and complexity of bacteria were similar in the ID and initial RC samples. The levels of LPS and LTA in ID were significantly higher than the initial RC samples (S1; P  < 0.05). Canal preparation was effective in significantly decreasing the levels of bacteria, LPS and LTA ( P  < 0.05). ICM did not provide additional reduction in the levels of bacteria and LPS ( P  > 0.05). However, a significant reduction in the levels of LTA was observed after ICM ( P  < 0.05). Conclusion: The microbial profile of infected dentine and root canals of teeth with irreversible pulpitis was complex, harbouring different species including Gram‐positive and Gram‐negative, cocci and bacilli, and facultative and strict anaerobes. Root canal preparation was effective in reducing the levels of bacteria, LPS and LTA from the root canals of teeth with pulpitis.